Peran Daya Saing Kultural dan Kapabilitas Dinamik dalam Meningkatkan Kinerja Organisasional - Agustinus Dedy Handrimurtjahjo; Engkos Achmad Kuncoro (Binus Business Review, 2012)
This paper develops a conceptual framework for intended study which will examine the effect cultural competitiveness on dynamic capabilities and organizational performance. Previous study argued that four variables of Cultural Competitiveness (entrepreneurship, innovativeness, market orientation and organizational learning) have a direct effect on organizational performance. Meanwhile, the other study argued that dimensions of entrepreneurial orientation have a significantly positive effect on dynamic capabilities to different extents, while organizational learning, which has significantly positive effect on dynamic capabilities, plays a partial mediating role between the two. These findings indicate that companies can build dynamic capabilities through different levels of organizational learning in the context of innovative and proactive atmosphere.